Women, Drugs and the Death Penalty: Framing Sandiford. Issue 3 (5th September 2017) - FLEETWOOD, JENNIFER; SEAL, LIZZIE
Abstract: This article examines the impact and significance of women subject to capital punishment for drug offences. Women are subject to the death penalty for drug offences; wherever data are available they describe low‐level offenders, primarily drug mules. Sandiford's death sentence prompts widespread discussion about her, her culpability and the appropriateness of her punishment drawing on drug war discourse, and death penalty tropes. Framing analysis reveals the powerful and persistent nature of gendered binaries. The use of capital punishment against female mules troubles the gendered binaries that underpin US‐led drug war discourse, and highlights the death penalty as a gendered punishment.